Progressive multifocal encephalopathy in a patient with non-Hodgkin follicular lymphoma - Trociukas, I.; Zirnis, A.E.; Beļajeva, L.; Rivkina, A.; Lejniece, S. (PH Akademperiodyka, 2023)
Summary. Progressive multifocal leukoencephalopathy (PML) is a rare and often fatal demyelinating disease of the central nervous system caused by John Cunningham virus (JCV). We present a case report of patient with non-Hodgkin follicular lymphoma, who developed PML after hematopoietic stem cell transplantation and rituximab-bendamustine therapy. JCV DNA was proven both in peripheral blood and cerebrospinal fluid. Patient with 4 years history of follicular lymphoma presented with progressing weakness in the right arm and leg and postural instability. Magnetic resonance imaging scans showed bilateral hyperintense lesions in the cerebellum and centrum semiovale consistent with findings in PML. JCV DNA was detected in patient peripheral blood and cerebrospinal fluid by real time polymerase chain reaction assay in CERBA laboratory (France). Human herpes simplex 6 and 7 DNA were also detected in peripheral blood by PCR. Patients condition rapidly deteriorated with exitus letalis after 3 months and 2 weeks from onset of symptoms. This case draws attention to risk for developing PML in patients with long-standing hematological malignancies.